The presence of ACE2 and regulatory miRNAs (miR-200c-3p and miR-421-5p) in the saliva of periodontitis patients post-COVID-19 vaccination - Boy M. Bachtiar; Natalina Haerani; Yuniarti Soeroso; Nada Ismah; Endang W. Bachtiar (Frontiers Media S.A., 2024)
The effectiveness of COVID-19 mRNA vaccines in individuals with periodontitis is crucial. This study evaluated the efficacy of the BNT162b2 vaccine in individuals with periodontitis who had been vaccinated at least 6 months earlier. Using real-time PCR, the association between the SARS-CoV-2 receptor angiotensin-converting enzyme 2 (ACE2) and miRNA-200c-3p and miRNA-421-5p as well as interleukin-6 (IL-6) was examined in the saliva of moderate (G1, n = 10) and severe (G2, n = 10) periodontitis subjects. Participants without periodontitis were included as a control group. The transcription levels of soluble ACE2 and IL-6 were higher in periodontitis participants than in control participants, but within periodontitis groups, only IL-6 expression was higher in G2 than in G1. A positive strong correlation between ACE2 and IL-6 was only observed in the G2 group (p = 0.008). The expression of miR-200c-3p but not miR-421-5p was higher in periodontitis individuals. Their relationship was positive but a strong correlation was only observed in the G2 group. In all periodontitis groups, a strong inverse correlation was observed between the two microRNAs and ACE2. However, receiver operating characteristic (ROC) analysis showed that only the relationship between ACE2 and miR-4215p had potential as a biomarker for the efficacy of the mRNA vaccine, with areas under the ROC curve of 0.92 and 0.80 in the G1 and G2 groups, respectively. Our study revealed that active and non-active periodontitis conditions do not interfere with the efficacy of the BNT162b2 vaccine for at least 6 months post-vaccination. This suggests that in individuals with periodontitis, soluble ACE2 in the saliva may serve as a preliminary indicator of vaccine response.